(untitled) (Nepalese Journal of Radiology, 2022)
Introduction: The coccyx, a triangular bone forming the last part of the vertebral column, acts as the weight-bearing structure when a person is seated, and is the site of insertion of the pelvic floor tendons and numerous ligaments attached to it. The main objective of this study was to investigate the morphology and morphometry of the coccyx on lumbar spine MRI images in asymptomatic individuals among Nepalese adults. Methods: This study was conducted retrospectively on the lumbar spine images of 190 adult population without a history of trauma in the coccyx region, from April to September 2019. The coccygeal vertebrae count, the number of bone segments, and intercoccygeal and joint fusions were determined from the sagittal plane images. In addition, the length and angles were also measured. Results: One hundred and ninety patients, with a mean age of 43.91 years, were enrolled in the study. Among the 4 types of coccyx; the most common type was type II (46.3%), followed by type I (40.5%). The coccyx was formed from 4 vertebral segments in 21.1% (n=41) individuals, 3 vertebral segments in 45.3% (n=86) individuals, 2 vertebral segments in 31.1% (n=59) individuals and 1 vertebral segment in 2.1% (n=4) individuals. Conclusions: In our study, type II coccyxes predominated. The prevalence of sacrococcygeal and intercoccygeal fusion, as well as the number of coccygeal vertebrae, were similar in the Nepalese population and the Western population.